"The Limits of my Language Mean the Limits of my World": Multilingualism in Medieval Iceland - Thorn, Katherine, 1989- (2016)
Multilingualism studies is a rapidly developing field. In recent years, exciting leaps have been made in approaching medieval European societies from the understanding that they were less monolingual than has previously been assumed, especially within western Christian sphere. This has furthered the study of cultural diversity and socio-linguistics in the Middle Ages. This thesis approaches medieval Iceland as a peripheral region within Europe. Nevertheless, it had strong practical and cultural ties with mainland Scandinavia and further abroad. In this thesis, I discuss how medieval Icelanders would have considered foreign languages and those people who could speak them. A particular link is made between language and Christian philosophical thought in light of the Tower of Babel story and its transmission, and also of the connection between multilingualism and kingship ideology as suggested in Konungs skuggsjá. A suggestion is made that multilingualism and the medieval Icelandic conception of their own language closely relate to the formation of social identity. Having established a theoretical framework, several saga protagonists are considered from the Íslendingasögur, fornaldarsögur, and Biskupasögur to analyse how their multilingualism is portrayed within the narrative. This then provides clues as to how medieval Icelanders viewed their own language. Rannsóknir á fjöltyngi hafa farið vaxandi á undanförnum áratugum. Á nýliðnum árum hefur átt sér stað áhugaverð framþróun í skilningi á fjöltyngi í kristnum miðaldasamfélögum Vesturlanda, en áður var talið að eintyngi hefði verið ríkjandi. Í ritgerðinni er fjallað um Ísland sem jaðarland sem eigi að síður er í sterku efnislegu og menningarlegu sambandi við Norðurlönd og önnur lönd í Evrópu. Grafist er fyrir um hvernig Íslendingar á miðöldum litu á erlend mál og þá sem töluðu þau. Sérstök tenging er við heimspekilega hugsun um tungumálið á miðöldum, ekki síst við söguna af Babelsturninum og birtingarmyndum hennar. Einnig er litið til sambands milli ...